The Effect of Jackfruit (Artocarpus heterophyllus) Seeds Flour as Supplementary Feed to the Meat Quality of Broiler Chickens Strain Cobb - Kharisma, Anastya Eka; Gofur, Abdul; Witjoro, Agung (Proceeding International Conference on Global Resource Conservation, 2013)
Broiler chickens are one of animal protein source which attracted people. So far, farmers have a constraint about the expensive price of feed, so farmers should be able to find an alternative way to reduce the feed costs. Seeds of jackfruit (Artocarpus heterophyllus) is an agricultural waste that has a high nutrient content. The aim of the research to know the effect of Jackfruit (Artocarpus heterophyllus) seeds flour as a supplementary feed to the meat quality of broiler chickens Cobb strain. This research is an experimental using Complete Randomized Design with five treatment and five replications each. Chickens are treated using jackfruit seed flour for 20 days, and then the meat was analized using proximate test. Data obtains from proximate test and analyze using one way ANOVA with LSD 5% perform if the result is significant. The results shows that jackfruit seeds flour as supplementary feed significantly affect the meat quality of broiler chickens on crude protein at treatment of 10% and crude fat at treatment of 30% but the treatments has no effect on water content, ash content, organic matter, carbohydrates, metabolism energy (ME).Keywords: Jackfruit (Artocarpus heterophyllus) Seeds Flour, Meat Quality, Supplementary FeedÂ